Motivation toward the extension of organic rice production in Northeast Thailand - Opal Suwunnamek; Poramate Asawaruangpipop (My University, 2017)
Purpose-Organic rice growers have continued their lives and organic agriculture way of production firmly, although there is a common way of rice production by using chemical fertilizers and pesticides in Thailand.Movtivation of these organic growers will be explored for concerned organizations to encourage more organic production in the country.Surin and Yasothon provinces were the study area as there is a large number of organic rice production in these 2 provinces.Methodology-Descriptive and quantitative analysis by Multiple regression analysis are applied.Findings-The results showed that the most influential factors that motivated organic production was due to farmer's opinion that organic agriculture is the way of sustainable production mode, a good relationship within the household and no excessive resources compared with chemicals.In addition, government support, health concern, organic being the new production trend, and cost reduction were also statistically significant factors.Conclusion-Facilitation from concerned organizations to motivate farmers to extend their production area from these factors are recommended.
Keywords: Agricultural Economics and Policy